2008
DOI: 10.1007/s11095-008-9742-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bioequivalence Assessment of Topical Dermatological Drug Products Using Dermatopharmacokinetics

Abstract: Comparative bioequivalence can be assessed conclusively with fewer treatment sites in fewer subjects with robust methods that should be less sensitive to inter-laboratory differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 21 publications
5
101
0
Order By: Relevance
“…21,22 Four healthy volunteers (female, age 23-44 years), with no history of dermatological disease, participated in the study, which was approved by the Local Research Ethics Committee (Cerrahpaşa Medical Faculty Ethics Committee, Istanbul, Turkey). Written informed consent was obtained from each subject.…”
Section: In Vivo Skin Penetration Studymentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Four healthy volunteers (female, age 23-44 years), with no history of dermatological disease, participated in the study, which was approved by the Local Research Ethics Committee (Cerrahpaşa Medical Faculty Ethics Committee, Istanbul, Turkey). Written informed consent was obtained from each subject.…”
Section: In Vivo Skin Penetration Studymentioning
confidence: 99%
“…23 Then the stratum corneum was sequentially stripped from the same area, 20 times with adhesive tapes (Scotch Book Tape; 3M Tegaderm) in accordance with the published studies. [21][22][23][24] The adhesive tapes were applied to the skin with vigorous rubbing by the gloved operator and then removed. To check the skin barrier function, TEWL measurements were recorded using an open chamber device (Tewameter) before the first tape strip (baseline value) and during the tape stripping procedure.…”
Section: In Vivo Skin Penetration Studymentioning
confidence: 99%
“…However, the drug concentration at each depth of the skin has been predicted using various mathematical equations [13][14][15][16][17][18]. We previously reported that the cutaneous disposition of topically applied drugs could be predicted using the difference method based on Fick's 2 nd law of diffusion, and also that the average drug concentration in the stratum corneum and viable epidermis/dermis could be determined separately [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative work has looked into the effect of epidermal turnover on percutaneous penetration [53], the clearance phase of the DPK profile [54] and into optimization of the DPK methods [55,56]. This work explored critical issues such as the time required for tape-stripping, cleaning procedures, and how the collected tape strips should be combined to reduce variability and improve analytical sensitivity.…”
Section: Dermatopharmacokineticsmentioning
confidence: 99%